Effects of L-Carnitine on Cardiac Apoptosis in Ischemic-Reperfused Isolated Rat Heart: L-carnitine and apoptosis - Najafi, Moslem; Garjani, Alireza; Dustar, Yousef (Iranian Journal of Pharmaceutical Sciences, 2007)
Carnitine is a vital biologic substance for transporting fatty acids into myocytes.It also facilitates fatty acids β-oxidation for energy production. In this study, effectsof L-carnitine (L-Car) on apoptosis in the ischemic isolated rat heart were investigated.Male Sprague-Dawley rats were divided into four groups and anesthetized bysodium pentobarbital. The heart was removed and mounted on a Langendorffapparatus then perfused by a modified Krebs-Henseleit (K/H) solution under aconstant pressure at 37 °C. In the control group, the hearts were perfused only bynormal K/H solution at stabilization, 30 min. regional ischemia and 120 min.reperfusion, while in each of the test groups, the hearts were perfused duringischemia-reperfusion with 0.5, 2.5 and 5 mM of L-Car-enriched K/H solution,respectively. At the end of reperfusion, immunohistochemical detection of apoptoticcells was performed by using an in situapoptosis detection kit. The number ofTUNEL-positive cardiomyocytes was counted in five random high-power fields ineach sample. In the control group, the number of apoptotic cells were 48±3 whileaddition of L-Car (0.5, 2.5 and 5 mM) to the solution reduced the number ofapoptotic cells to 6±1, 4±1 and 3±1, respectively (p<0.001 for all concentrations).There was no significant difference between and within test groups using ANOVAone-way. Considering these results, we conclude that L-Car has a protective effectagainst cardiac ischemia-reperfusion induced injuries as a reduction of apoptoticcardiomyocytes.